Neuroprotective-Neurorestorative Effects Induced by Progesterone on Global Cerebral Ischemia: A Narrative Review - Pedro Montes; Emma Ortíz-Islas; Citlali Ekaterina Rodríguez-Pérez; Elizabeth Ruiz-Sánchez; Daniela Silva-Adaya; Pavel Pichardo-Rojas; Victoria Campos-Peña (MDPI AG, 2023)
Progesterone (P4) is a neuroactive hormone having pleiotropic effects, supporting its pharmacological potential to treat global (cardiac-arrest-related) cerebral ischemia, a condition associated with an elevated risk of dementia. This review examines the current biochemical, morphological, and functional evidence showing the neuroprotective/neurorestorative effects of P4 against global cerebral ischemia (GCI). Experimental findings show that P4 may counteract pathophysiological mechanisms and/or regulate endogenous mechanisms of plasticity induced by GCI. According to this, P4 treatment consistently improves the performance of cognitive functions, such as learning and memory, impaired by GCI. This functional recovery is related to the significant morphological preservation of brain structures vulnerable to ischemia when the hormone is administered before and/or after a moderate ischemic episode; and with long-term adaptive plastic restoration processes of altered brain morphology when treatment is given after an episode of severe ischemia. The insights presented here may be a guide for future basic research, including the study of P4 administration schemes that focus on promoting its post-ischemia neurorestorative effect. Furthermore, considering that functional recovery is a desired endpoint of pharmacological strategies in the clinic, they could support the study of P4 treatment for decreasing dementia in patients who have suffered an episode of GCI.